Validity of smartwatch-derived estimates of lactate threshold heart rate and pace compared to graded exercise testing - Lu, C.; Cui, W.; Zhu, Z.; Wu, Y.; Xing, Q.; Pan, B.; Shen, Y. (Frontiers in Physiology, 2025)
Background: Quantifying exercise intensity through the lactate threshold (LT) is crucial for optimizing athletic training regimes. Traditional methods like maximal lactate steady state and graded exercise testing are valid but invasive and costly. Advances in smartwatch technology offer a non-invasive alternative for monitoring LT, though their measurement protocols and outcomes have been less validated.